2011
DOI: 10.1002/ajmg.b.31201
|View full text |Cite
|
Sign up to set email alerts
|

No association between a common single nucleotide polymorphism, rs4141463, in the MACROD2 gene and autism spectrum disorder

Abstract: The Autism Genome Project (AGP) Consortium recently reported genome-wide significant association between autism and an intronic single nucleotide polymorphism marker, rs4141463, within the MACROD2 gene. In the present study we attempted to replicate this finding using an independent case-control design of 1,170 cases with autism spectrum disorder (ASD) (874 of which fulfilled narrow criteria for Autism (A)) from five centers within Europe (UK, Germany, the Netherlands, Italy, and Iceland), and 35,307 controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
(51 reference statements)
2
24
0
Order By: Relevance
“…This may be due to population effects, such as different allele compositions, or to limited power afforded by too small numbers of participants. The first possible explanation is consistent with the associating SNP rs1718101 in intron 1 found in the AGP cohort of ASD patients [Anney et al, 2012], with the SNPs rs2710093 and rs2253031 in intron 14 [Sampath et al, 2013], and the differences among different European populations reported with SNP rs4141463 in MACROD2 [Curran et al, 2011;Anney et al, 2012;Prandini et al, 2012].…”
Section: Association Of Cntnap2 With Neurodevelopmental Disorderssupporting
confidence: 78%
“…This may be due to population effects, such as different allele compositions, or to limited power afforded by too small numbers of participants. The first possible explanation is consistent with the associating SNP rs1718101 in intron 1 found in the AGP cohort of ASD patients [Anney et al, 2012], with the SNPs rs2710093 and rs2253031 in intron 14 [Sampath et al, 2013], and the differences among different European populations reported with SNP rs4141463 in MACROD2 [Curran et al, 2011;Anney et al, 2012;Prandini et al, 2012].…”
Section: Association Of Cntnap2 With Neurodevelopmental Disorderssupporting
confidence: 78%
“…Curran et al (2011) attempted to replicate the association using an independent case–control design with 1170 European cases and 35 307 controls and Prandini et al (2012) sought to replicate genetic markers from recent genomewide and candidate-gene studies in the Italian Autism Network cohort, consisting of 233 probands, 423 parents, and 90 siblings. In both studies, cases met the Diagnostic and Statistical Manual of Mental Disorders, 4th ed.…”
Section: Discussionmentioning
confidence: 99%
“…The drive for large samples, notably in molecular genetics research, has encouraged the combination of data collected in different countries and languages (e.g. Curran et al, 2011). The question of whether ASD presents differently in different cultures has never been more pressing or more amenable to empirical investigation.…”
Section: Autism 18(1)mentioning
confidence: 99%